Emerging Green Techniques for the Extraction of Antioxidants from Agri-Food By-Products as Promising Ingredients for the Food Industry - Serena Carpentieri; Farid Soltanipour; Giovanna Ferrari; Gianpiero Pataro; Francesco Donsì (MDPI AG, 2021)
Nowadays, the food industry is heavily involved in searching for green sources of valuable compounds, to be employed as potential food ingredients, to cater to the evolving consumers' requirements for health-beneficial food ingredients. In this frame, agri-food by-products represent a low-cost source of natural bioactive compounds, including antioxidants. However, to effectively recover these intracellular compounds, it is necessary to reduce the mass transfer resistances represented by the cellular envelope, within which they are localized, to enhance their extractability. To this purpose, emerging extraction technologies, have been proposed, including Supercritical Fluid Extraction, Microwave-Assisted Extraction, Ultrasound-Assisted Extraction, High-Pressure Homogenization, Pulsed Electric Fields, High Voltage Electrical Discharges. These technologies demonstrated to be a sustainable alternative to conventional extraction, showing the potential to increase the extraction yield, decrease the extraction time and solvent consumption. Additionally, in green extraction processes, also the contribution of solvent selection, as well as environmental and economic aspects, represent a key factor. Therefore, this review focused on critically analyzing the main findings on the synergistic effect of low environmental impact technologies and green solvents towards the green extraction of antioxidants from food by-products, by discussing the main associated advantages and drawbacks, and the criteria of selection for process sustainability.